The Influence of the Scientific Approach on the Learning Interest - Muhammad Yusup; Marzani Marzani; Mutia Paramita (AL-ISHLAH: Jurnal Pendidikan, 2021)
This study aims to see the effect of the approach in Islamic Education on the learning interest of junior high school students a. This type of research uses a quantitative approach. To obtain the data studied, the researcher took population data of 170 students, so as a test instrument taken from a research sample of 66 students, this was no longer used as a research sample. So the remainder of the number used as the sample for the instrument trial was used as a research sample, which might be 104 students. The results revealed correlation between the scientific approach (X) and student learning interest (Y) which was 0.332, which indicates a low level. The correlation coefficient is positive, which means there is a positive effect. The correlation that occurs is significant because the calculated value is greater than the table, namely 2.662 2.00. Based on the results of the data analysis provide that there is an influence between the scientific approach variable, the student learning interest variable. Based on the results of this study, the party in charge of junior high school implements scientific learning to improve learning outcomes.